(untitled) (The Pakistan Development Review, 1988)
While demand estimates are used in policy making in a number of areas, there has not been a substantial literature on demand patterns and responses in Pakistan. We present estimates for thirteen classes of goods, based on a complete demand system, a modification of the Unear Expenditure System, using maximum likelihood techniques and observations at the household level for Pakistan and urban and rurll areas for 1976.